Chemical Compounds, Antioxidant Activities, and Inhibitory Activities Against Xanthine Oxidase of the Essential Oils From the Three Varieties of Sunflower (Helianthus annuus L.) Receptacles - Liu, Xin-Sheng; Gao, Bo; Dong, Zhan-De; Qiao, Zi-An; Yan, Min; Han, Wei-Wei; Li, Wan-Nan; Han, Lu (Frontiers in Nutrition, 2021)
Background/Aim: Essential oils of sunflower receptacles (SEOs) have antibacterial and antioxidant potential. However, the differences of biological activities from the different varieties of sunflowers have not been studied till now. The purpose of this study was to compare the differences of chemical compounds, antioxidant activities and inhibitory activities against xanthine oxidase (XO) of SEOs from the three varieties of sunflowers, including LD5009, SH363 and S606. Methods: SEOs were extracted using the optimal extraction conditions selected by response surface methodology (RSM). Chemical compounds of SEOs were identified from the three varieties of sunflowers by gas chromatography-mass spectrometry (GC-MS). Antioxidant activities of SEOs were detected by ABTS, DPPH and iron ion reduction. Inhibitory activities of SEOs against XO was measured by using ultraviolet spectrophotometer. XO inhibitors were selected from the main chemical compounds of SEOs by high-throughput selections and molecular simulation docking. Results: The extraction yields of SEOs from LD5009, SH363 and S606 were 0.176%, 0.319% and 0.580% respectively. A total of 101 chemical compounds of SEOs were identified from the three varieties of sunflowers. In addition, the results of inhibitory activities against XO showed that SEOs can reduce uric acid significantly. Eupatoriochromene may be the most important chemical compounds of SEOs for reducing uric acid. The results of antioxidant activities and inhibitory activities against XO showed that SEOs of LD5009 had the strongest antioxidant and XO inhibitory activities. Pearson correlation coefficient (r>0.95) showed that γ-terpinene, (e)-citral and L-bornyl were highly correlated with antioxidant activities and XO inhibitory ability. Conclusion: SEOs had antioxidant activities and XO inhibitory ability. It would provide more scientific information for utilization and varieties selection of sunflowers, which would increase food quality of sunflowers and incomes of farmers.